Soft Template‐Based Synthesis of Mesoporous Phosphorus‐ and Boron‐Codoped NiFe‐Based Alloys for Efficient Oxygen Evolution Reaction - Kang, Yunqing; Guo, Yanna; Zhao, Jingjing; Jiang, Bo; Guo, Jingru; Tang, Yi; Li, Hexing; Malgras, Victor; Amin, Mohammed A.; Nara, Hiroki; Sugahara, Yoshiyuki; Yamauchi, Yusuke; et al. (Small (Weinheim an der Bergstrasse, Germany), 2022)
Controlling the morphology, composition, and crystalline phase of mesoporous nonnoble metal catalysts is essential for improving their performance. Herein, well‐defined P‐ and B‐codoped NiFe alloy mesoporous nanospheres (NiFeB‐P MNs) with an adjustable Ni/Fe ratio and large mesopores (11 nm) are synthesized via soft‐template‐based chemical reduction and a subsequent phosphine‐vapor‐based phosphidation process. Earth‐abundant NiFe‐based materials are considered promising electrocatalysts for the oxygen evolution reaction (OER) because of their low cost and high intrinsic catalytic activity. The resulting NiFeB‐P MNs exhibit a low OER overpotential of 252 mV at 10 mA cm−2, which is significantly smaller than that of B‐doped NiFe MNs (274 mV) and commercial RuO2 (269 mV) in alkaline electrolytes. Thus, this work highlights the practicality of designing mesoporous nonnoble metal structures and the importance of incorporating P in metallic‐B‐based alloys to modify their electronic structure for enhancing their intrinsic activity. The well‐defined mesoporous P‐ and B‐ codoped NiFe alloy nanospheres with adjustable Ni/Fe ratio and tunable pore size are successfully synthesized. The addition of P to the system allows for the tuning of the electronic structure of the active sites and enhances the electrical conductivity, leading to a significant increase in intrinsic oxygen evolution reaction performance.